Assembleia de aranhas de solo (Arachnida, Araneae) associada a fragmentos florestais na região Norte de Mato Grosso - Santos, Genefer Elecianne Raíza dos (2019)
The brazilian agrobusiness stands out in the main rankings in production and exportation, this condition generates a series of discussions about biodiversity conservation, being that the country also holds the biggest tropical patrimony in the world. But the advance of the agricultural frontier in those same regions results in landscape changes, reducing the conectivity between habitats and increasing the number of fragments that affect the demographic parameters of mortality and natality from different species, therefore, the ecosystems dynamics. There is an urgency that the policies include urban regions, this forest fragment areas in urban matrix will become even more important to protect the local and global ecosystems. Besides the knowledge of the biodiversity associated, the definition of species or groups of species usefull in the biomonitoring of the dynamic of these habitats becomes fundamental, because the bioindicators are utilized to quantify changes in the ecosystems in response to different types of disturbances. The spiders, just like other arachnids, share a series of attributes that makes them apropriated to indicate ecological integrity in ecosystems, high wealth, easy sampling and sensibility to environmental changes, as well as occuring throughout the whole year. Thus, this study evaluated a composition, wealth and abundance of soil spiders (Arachnida, Araneae) associated to matrices of forest fragments inserted in urban and rural matrix, in the northern region of Mato Grosso, Brazil. Samples occurred between July/2017 and November/2017 in nine areas, including fragments inserted in urban and rural matrix, and continuous forest areas, using mini-Winkler Extractor and pitfall traps. A total of 1,561 spiders were sampled and distributed in 25 families, 36 genera and 56 species, evidencing the need to save these habitats, both in urban and rural areas, as well as in forest areas. The results obtained are presented in two manuscripts: (i) Soil spiders (Arachnida, Araneae) on an environmental gradient in the deforestation arc of the Amazon forest in Mato Grosso; (ii) Soil spiders (Arachnida, Araneae) associated with urban forest fragments in the northern region of Mato Grosso, Brazil.